Effect of Ultrasonic Combined with Solvent on Gutta-Percha and Bioceramic Sealer Removal in Middle and Apical Third of the Root Canal: An ex vivo study - Fibryanto, Eko; Widyastuti, Wiena; Hidayat, Adi; Hastuty, Lisiana (Journal of Dentistry Indonesia, 2024)
Objective: This study aims to investigate the effectiveness of ultrasonic tip with and without solvent in removing gutta-perca and bioceramic sealer from the middle and apical third of the root canals. Methods: This is a true experimental study with randomized pretest-posttest control group design. Eighteen freshly extracted straight single-rooted mandibular first premolars were confirmed by CBCT and selected. The teeth were decoronated until a length of 16 ± 0.5mm. The teeth were prepared and obturated using gutta-percha and bioceramic sealer with a hydraulic condensation technique. Pre-instrumentation CBCT imaging of all teeth was carried out to obtain the initial volume of the obturation material. After incubating for 30 days, the treated teeth were randomly divided into three groups (n = 6): ultrasonic and xylene, ultrasonic and orange oil, and ultrasonic only. Post-instrumentation CBCT was carried out and the amount of obturation material removed was calculated using CT Analyser. The two-way ANOVA was used to determine the solvent and location interaction. Results: The results showed that there was no significant difference among the groups based on the treatment and location (p > 0.05). In addition, no significant interaction was found in relation to the cleanliness of the root canal (p > 0.05). Conclusion: There was no difference in the effectiveness of ultrasonic obturation material cleaning with and without endodontic solvents. Based on the results, the obturation material with the most residue is a sealer.